Using Seasonal Climate Variability Forecasts to Plan Forest Plantation Establishment - Norman Breuer; Matthew Langholtz; David Zierden; Clyde Fraisse (EDIS)
Atmospheric scientists are now able to predict seasonal climate variations, with a relatively high level of skill. Knowledge of climatic conditions allows us to develop a seasonal management strategy for forest plantations and managed natural forests. Areas of application include seedling establishment, preparing for pests and diseases, fire management, harvest schedules and inventory management. This publication provides strategies to consider for pine plantation establishment in Florida and southern Alabama and Georgia. Seasonal climate conditions can be better predicted for this region because it is affected by the El Niño Southern Oscillation (ENSO) phenomenon. This document is ABE354, one of a series of the Agricultural and Biological Department, Florida Cooperative Extension Service, Institute of Food and Sciences, University of Florida. Published November 2004.